Experimental evaluation of the dosimetric impact of intrafraction prostate rotation using film measurement with a 6DoF robotic arm. Issue 12 (30th October 2020) - Shi, Kehuan; Dipuglia, Andrew; Booth, Jeremy; Alnaghy, Saree; Kyme, Andre; Keall, Paul; Nguyen, Doan Trang
Abstract : Purpose: Tumor motion during radiotherapy can cause a reduction in target dose coverage and an increase in healthy tissue exposure. Tumor motion is not strictly translational and often exhibits complex six degree‐of‐freedom (6DoF) translational and rotational motion. Although the dosimetric impact of prostate tumor translational motion is well investigated, the dosimetric impact of 6DoF motion has only been studied with simulations or dose reconstruction. This study aims to experimentally quantify the dose error caused by 6DoF motion. The experiment was designed to test the hypothesis that 6DoF motion would cause larger dose errors than translational motion alone through gamma analyses of two‐dimensional film measurements. Methods: Four patient‐measured intrafraction prostate motion traces and four VMAT 7.25 Gy/Fx SBRT treatment plans were selected for the experiment. The traces represented typical motion patterns, including small‐angle rotations (<4°), transient movement, persistent excursion, and erratic rotations (>6°). Gafchromic film was placed inside a custom‐designed phantom, held by a high‐precision 6DoF robotic arm for dose measurements in the coronal plane during treatment delivery. For each combination of the motion trace and treatment plan, two film measurements were made, one with 6DoF motion and the other with the three‐dimensional (3D) translation components of the same trace. A gamma pass rate criteria of 2% relative dose/2 mm distance‐to‐agreement was used in this study and evaluated for each measurement with respect to the static reference film. Two test thresholds, 90% and 50% of the reference dose, were applied to investigate the difference in dose coverage for the PTV region and surrounding areas, respectively. The hypothesis was tested using a Wilcoxon signed‐rank test. Results: For each of the 16 plan and motion trace pairs, a reduction in the gamma pass rate was observed for 6DoF motion compared with 3D translational motion. With 90% gamma‐test threshold, the reduction was 5.8% ± 7.1% ( P < 0.01). With 50% gamma‐test threshold, the reduction was 4.1% ± 4.8% ( P < 0.01). Conclusion: For the first time, the dosimetric impact of intrafraction prostate rotation during SBRT treatment was measured experimentally. The experimental results support the hypothesis that 6DoF tumor motion causes higher dose error than translation motion alone.